2014
DOI: 10.1055/s-0034-1376421
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Dural Sinus Thrombosis following Resection of Cerebellopontine Angle Tumors

Abstract: Objective Lateral sinus thrombosis is a potentially devastating but seldom studied complication of cerebellopontine angle (CPA) tumor surgery. Systemic anticoagulation in the early postoperative period has often been avoided due to the potential risks of intracranial hemorrhage. Design Retrospective review. Setting Tertiary referral center. Main Outcome Measures The goal of this study was to identify the frequency, treatment, and outcomes in patients who develop postoperative venous sinus thrombosis following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…First-line management of cerebral venous sinus thrombosis involves careful anticoagulation. 76 , 77 We have also previously reported on the potential role of optic nerve sheath fenestration in post VS-resection cerebral venous sinus thrombosis with threatened vision. 5
Figure 4 Magnetic resonance venogram following resection of a left vestibular schwannoma showing absence of filling of the left transverse venous sinus (arrows) due to a transverse venous sinus thrombosis.
…”
Section: Papilledemamentioning
confidence: 90%
See 2 more Smart Citations
“…First-line management of cerebral venous sinus thrombosis involves careful anticoagulation. 76 , 77 We have also previously reported on the potential role of optic nerve sheath fenestration in post VS-resection cerebral venous sinus thrombosis with threatened vision. 5
Figure 4 Magnetic resonance venogram following resection of a left vestibular schwannoma showing absence of filling of the left transverse venous sinus (arrows) due to a transverse venous sinus thrombosis.
…”
Section: Papilledemamentioning
confidence: 90%
“…First-line management of cerebral venous sinus thrombosis involves careful anticoagulation. 76,77 We have also previously reported on the potential role of optic nerve sheath fenestration in post VS-resection cerebral venous sinus thrombosis with threatened vision. 5…”
Section: Papilledemamentioning
confidence: 90%
See 1 more Smart Citation
“…[ 3 , 13 ] Early retrospective studies reported pCVST incidence between 5.2% and 11.6% with more recent prospective studies revealing much higher rates between 32.4% and 38.9%. [ 1 , 4 , 7 , 12 ] This discrepancy is, in part, a result of the overwhelmingly asymptomatic nature of pCVST where capturing the diagnosis is largely dependent on the standardization of postoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Some advocate diagnostic vigilance and therapeutic anticoagulation or antiplatelet therapy regardless of clinical symptoms as supported by trials involving sCVST. [ 5 , 6 , 12 ] However, others choose to treat only if it is symptomatic noting that therapeutic anticoagulation in the immediate postoperative period is not without risk of significant intracranial hemorrhage and that available evidence point toward pCVST being a largely benign and asymptomatic process with up to 61% rate of recanalization at 1 year follow-up without any intervention. [ 2 , 3 , 7 ] Indeed, in two large prospective studies, Benjamin et al .…”
Section: Discussionmentioning
confidence: 99%